2015
DOI: 10.1007/s40264-015-0366-9
|View full text |Cite
|
Sign up to set email alerts
|

Hepatotoxicity Associated with the Use of Anti-TNF-α Agents

Abstract: Medications to inhibit the actions of tumour necrosis factor alpha have revolutionized the treatment of several pro-inflammatory autoimmune conditions. Despite their many benefits, several serious side effects exist and adverse reactions do occur from these medications. While many of the medications’ potential adverse effects were anticipated and recognized in clinical trials prior to drug approval, several more rare adverse reactions were recorded in the literature as the popularity, availability and distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 53 publications
1
54
0
1
Order By: Relevance
“…Six of the nine cases went on to emergent transplantation, with the other three recovering liver function with steroid therapy. Given the wide range of latency, this may suggest an idiosyncratic DILI rather than a dose‐dependent toxicity, which has been described in other studies as well …”
Section: Tumor Necrosis Factor Alpha Inhibitorsmentioning
confidence: 68%
See 3 more Smart Citations
“…Six of the nine cases went on to emergent transplantation, with the other three recovering liver function with steroid therapy. Given the wide range of latency, this may suggest an idiosyncratic DILI rather than a dose‐dependent toxicity, which has been described in other studies as well …”
Section: Tumor Necrosis Factor Alpha Inhibitorsmentioning
confidence: 68%
“…N‐acetyl‐cysteine has been shown to improve transplant‐free survival for patients not only with acetaminophen‐induced ALF but also with non‐acetaminophen ALF; however, patients with liver injury due to biologics have not been included in these studies . Corticosteroids have also been administered with better results in patients with DILI or AIH from TNF‐α inhibitor therapy . Data from a single‐center retrospective cohort study support these findings and also showed that corticosteroids were most effective for severe liver injury with peak total bilirubin >243 μmol/L .…”
Section: Management Of Biologic‐induced Liver Injurymentioning
confidence: 94%
See 2 more Smart Citations
“…While biological agent such as infliximab may be an appropriate option for patients with liver disorder history, it is still important to be cautious about the risk of HBV reactivation and other adverse effects [5,6] . Though the incidence of liver injury is relatively low, the existing several cases suggest that liver injury has a strong correlation with anti-TNF-α medications [7,8] . In addition, it is suggested that some patients lack a complete response to infliximab treatment.…”
Section: Introductionmentioning
confidence: 99%